Invasive red king crab affects lumpsucker recruitment by egg consumption - Mikkelsen, Nina; Pedersen, Torstein (Marine Ecology Progress Series, 2012)
The invasive red king crab Paralithodes camtschaticus preys on lumpsucker Cyclopterus lumpus eggs. We tested the hypothesis this egg consumption may hamper the recruitment of lumpsucker. Methods applied included field work, laboratory experiments and modelling of egg consumption. Crabs were sampled and feeding behaviour was studied by means of a remotely operated vehicle and SCUBA divers in a field survey carried out in Varanger Fjord, Norway, in 2003. Laboratory experiments were carried out in 2006 to study the digestion of lumpsucker eggs by red king crabs, and a stomach evacuation model was fitted to the experimental data. Using data from the field and laboratory studies, an egg consumption model was used to quantify the amount of lumpsucker eggs consumed by king crabs in Varanger Fjord. The uncertainty in model input data was assessed using a Monte Carlo simulation. Sex or sampling area did not significantly affect egg predation. A total of 7.9% of all crab stomachs contained an average of 20 lumpsucker eggs, but the number of eggs per stomach varied widely. The average time required to evacuate lumpsucker eggs at 6°C in the laboratory experiment was ~10 h. In 2003, king crabs in Varanger Fjord consumed lumpsucker roe equivalent to approximately one-third of commercial catches during the same period. Red king crab predation on lumpsucker eggs may hamper lumpsucker recruitment in northern Norwegian waters.